Factors and Challenges in Road Crash Incidents: Basis for Enhanced Interventions - Segun, William M.; Dela Cruz, Fermel V.; Golla, Nathaniel S.; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examined the factors that led to road crash incidents in Metro Manila, focusing on human behavior, public awareness and attitudes, road infrastructure and Mdesign, technological interventions, and the implementation of enforcement measures. The findings indicated that human error was the primary cause of road crashes, with speeding, driving under the influence of alcohol or drugs, distracted driving, failure to adhere to traffic rules, and aggressive driving behaviors identified as significant factors. We also found that road infrastructure and design, public awareness and attitudes, technological interventions, and enforcement measures significantly contribute to road crash incidents. The study further explored the challenges encountered by the Philippine National Police Highway Patrol Group in reducing road crash incidents. The study identified significant challenges in human behavior, public awareness, road infrastructure and design, technological interventions, and enforcement measures and found strong positive relationships between these factors and road crash incidents. We deemed it crucial to address these challenges to impact road safety and reduce accidents significantly. The research highlighted the importance of addressing human behavior, public awareness, road infrastructure and design, technological interventions, and enforcement measures to enhance road safety and reduce road crash incidents in Metro Manila. By focusing on these factors and addressing the identified challenges, the PNP Highway Patrol Group could implement enhanced interventions and promote a safer transportation environment for all road users.